2014
DOI: 10.1007/s00244-014-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicopathological Alterations Induced by High Dose Dietary T-2 Mycotoxin and its Residue Detection in Wistar Rats

Abstract: T-2 toxin is one of the most potent cytotoxic and food-borne mycotoxins. Most experimental studies on the T-2 toxin have been performed at extremely low doses (ppb level). However, several field reports of contaminated feed have shown concentration of T-2 toxin to be as high as ≥20 ppm. Therefore, the impact of high dose T-2 toxin (20 ppm) after subacute exposure was investigated in an experimental setup with respect to growth performance, oxidative stress, and detailed pathomorphology in young male Wistar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
4
11
0
1
Order By: Relevance
“…However, the histological examination of these tissues did not show any dystrophic changes indicating that reduction in plasma proteins is likely a result of disruption of protein synthesis and not directly related to tissue damage. Our findings are in agreement with several studies reporting the decrease in protein concentration in liver and plasma of mammals and birds after T‐2 toxin oral treatment (e.g., Atroshi et al., ; Chandratre et al., ; Pande, Kurkure, & Bhandarkar, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the histological examination of these tissues did not show any dystrophic changes indicating that reduction in plasma proteins is likely a result of disruption of protein synthesis and not directly related to tissue damage. Our findings are in agreement with several studies reporting the decrease in protein concentration in liver and plasma of mammals and birds after T‐2 toxin oral treatment (e.g., Atroshi et al., ; Chandratre et al., ; Pande, Kurkure, & Bhandarkar, ).…”
Section: Discussionsupporting
confidence: 93%
“…during 24–48 hr. The increase in lipid peroxidation was also observed in the liver of rats where lipid peroxidation was determined by analysis of TBARS (Chandratre et al., ; Rizzo et al., ). Our findings are in accordance with previous studies on lipid peroxidation as the increase in TBARS (28%) was observed in the liver of the trout at T‐2 toxin concentration 1.8 mg/kg.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A decrease in weight gain caused by trichothecenes has been described in several species, including rats. However, adult animals and prolonged exposure to toxin were used in most studies [4,5]. In our study, after treatment on the first postnatal day, growth impairment did not occur at once, but with a delay of about 7 days.…”
Section: Discussionmentioning
confidence: 61%